Media Literacy and the Internet Usage about Baby Care: Generation Y Mothers - Naile Bilgili; Fatma Avşar (Journal of Medical Education and Family Medicine)
Objective: This study was conducted to determine media literacy and internet usage related to health and baby care issues.Methods: This was a cross-sectional descriptive study. It was conducted on 175 Generation Y mothers (born between 1981 and 1995). The data were collected via the Media Literacy Level Determination Scale in five Facebook groups via online questionnaires. Mann‒Whitney U and Kruskal‒Wallis tests were used for data analysis.Results: The mean age of the mothers was 30 years. Mothers used social media sites (30.3%) on the internet the most. More than half of the mothers preferred health institutions (33.8%) or scientific websites (32.5%) for obtaining information. Mothers frequently investigated issues related to disease (12.6%) and infant‒child nutrition (10.9%). The mean score of the scale was 65.7 ± 11.6. Media literacy, education level and internet usage year were not statistically significant (P > .05).Conclusion: The media literacy level of the mothers was medium. Media literacy levels are higher among mothers who have graduated from university and have used the internet for more than five years. Nurses should consider that generation Y mothers can easily access information via social media.